The INTERNATIONAL MISSION study: minimally invasive surgery in ovarian neoplasms after neoadjuvant chemotherapy. Issue 1 (January 2019) - Fagotti, A; Gueli Alletti, S; Corrado, G; Cola, E; Vizza, E; Vieira, M; Andrade, C E; Tsunoda, A; Favero, G; Zapardiel, I; Pasciuto, T; Scambia, G
Abstract : Objectives: The aim of this retrospective multicenter study was to investigate the extent, feasibility, and outcomes of minimally invasive surgery at the time of interval debulking surgery in different gynecological cancer centers. Methods/Materials: In December 2016, 20 gynecological cancer centers were contacted by e-mail, to participate in the INTERNATIONAL MISSION study. Seven centers confirmed and five were included, with a total of 127 patients diagnosed with advanced epithelial ovarian cancer after neoadjuvant chemotherapy and minimally invasive interval surgery. Only women with a minimum follow-up time of 6 months from interval surgery or any cancer-related event before 6 months were included in the survival analysis. Baseline characteristics, chemotherapy, and operative data were evaluated. Survival analysis was evaluated using the Kaplan–Meier method. Results: All patients had optimal cytoreduction at the time of interval surgery: among them, 122 (96.1%) patients had no residual tumor. Median operative time was 225 min (range 60 – 600) and median estimated blood loss was 100 mL (range 70 – 1320). Median time to discharge was 2 days (1–33) and estimated median time to start chemotherapy was 20 days (range 15 – 60). Six (4.7%) patients experienced intraoperative complications, with one patient experiencing two serious complications (bowel and bladder injury at the same time). There were six (4.7%) patients with postoperative short-term complications: among them, three patients had severe complications. The conversion rate to laparotomy was 3.9 %. Median follow-up time was 37 months (range 7 – 86): 74 of 127 patients recurred (58.3%) and 31 (24.4%) patients died from disease. Median progression-free survival was 23 months and survival at 5 years was 52 % (95% CI: 35 to 67). Conclusions: Minimally invasive surgery may be considered for the management of patients with advanced ovarian cancer who have undergone neoadjuvant chemotherapy, when surgery is limited to low-complexity standard cytoreductive procedures.